2022
DOI: 10.1002/ece3.8742
|View full text |Cite
|
Sign up to set email alerts
|

Trophic niche partitioning between two prey and their incidental predators revealed various threats for an endangered species

Abstract: Documenting trophic niche partitioning and resource use within a community is critical to evaluate underlying mechanisms of coexistence, competition, or predation. Detailed knowledge about foraging is essential as it may influence the vital rates, which, in turn, can affect trophic relationships between species, and population dynamics. The aims of this study were to evaluate resource and trophic niche partitioning in summer/autumn between the endangered Atlantic‐Gaspésie caribou (Rangifer tarandus caribou) po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 130 publications
0
4
0
Order By: Relevance
“…Demonstrated links between nutrition and caribou demography remain weak but warrant further research. Evidence from western Canada suggests caribou foraging strategies can increase overlap with predators (bears in this case) and increase predation on caribou (Rioux et al, 2022). An alternate nutritional mechanism, as proposed by Heard and Zimmerman (2021), invokes declining forage availability due to risk‐sensitive foraging by caribou, whereby the increased abundance of predators has impacted caribou caloric intake.…”
Section: Discussionmentioning
confidence: 98%
“…Demonstrated links between nutrition and caribou demography remain weak but warrant further research. Evidence from western Canada suggests caribou foraging strategies can increase overlap with predators (bears in this case) and increase predation on caribou (Rioux et al, 2022). An alternate nutritional mechanism, as proposed by Heard and Zimmerman (2021), invokes declining forage availability due to risk‐sensitive foraging by caribou, whereby the increased abundance of predators has impacted caribou caloric intake.…”
Section: Discussionmentioning
confidence: 98%
“…Direct observations revealed that the contribution rates of Diptera, Orthoptera, and Lepidoptera were highest, while stable isotope analysis showed that the contribution rates of Orthoptera, Hemiptera, and Hymenoptera were highest. This difference can be explained by methodological differences; stable isotope analyses reflect the food resources assimilated by animals rather than the food consumed by animals [42,43], while the direct observation method records food resources that are consumed. Lepidoptera had the lowest contribution rate in the stable isotope analysis (2.29% for S. yunnanensis and 4.12% for S. nagaensis).…”
Section: Discussionmentioning
confidence: 99%
“…For the remaining species pairs, within-habitat segregation across horizontal space and to a lesser extent vertical stratification across foraging strata were the most likely mechanisms of species coexistence, with limited support for niche partitioning across diet and activity patterns. Quantifying niche overlap indices along multiple niche dimensions provides a mechanistic understanding of community structuring [ 28 , 60 ]. Together, our results suggest partitioning across multiple levels of spatial organization is a key mechanism that can give rise to the stable coexistence of closely related species in diverse communities.…”
Section: Discussionmentioning
confidence: 99%